Towards a new paradigm: The inflation shock as a catalyst? - Jérôme Creel; François Geerolf; Sandrine Levasseur; Xavier Ragot; Francesco Saraceno (Forum for a New Economy, 2024)
During the recent inflation episode, the paradigm of separated objectives for monetary and fiscal policies has shown some limits. Fiscal policies have helped mitigate inflation. We advocate for the emergence of a new paradigm that gives equal consideration to fiscal and monetary policies and their interactions. These interactions and their respective spillover effects demand better political coordination and a good dose of pragmatism, in contrast with the binding rules embedded in the separation paradigm so present in the European governance framework. The latter should give more leeway to supply-driven fiscal policies and learn from the US experience.
Keywords: E50; E60; H12; 330; fiscal policy; monetary policy; inflation; Tinbergen; coordination